2014
DOI: 10.2989/16085906.2014.927777
|View full text |Cite
|
Sign up to set email alerts
|

Jobs, food, taxis and journals: Complexities of implementing Stepping Stones and Creating Futures in urban informal settlements in South Africa

Abstract: This paper seeks to refocus debates on structural interventions away from 'assessing' their effectiveness towards understanding processes around how such interventions are implemented. Implementation Science is focused on understanding potential challenges of translating interventions from highly controlled conditions into 'real life' settings. Using the case study of Stepping Stones and Creating Futures a structural and behavioural intervention to reduce intimate partner violence and HIV risk behaviours among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Pilot results from long-term qualitative and quantitative research have been published [14, 20, 41]. Analysis showed men’s mean earnings in the past month increased by 247% from R411 (~$40) to R1015 (~$102), and women’s by 278% R 174 (~$17) to R 484 (about $48) (trend test, p  < 0.0001).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pilot results from long-term qualitative and quantitative research have been published [14, 20, 41]. Analysis showed men’s mean earnings in the past month increased by 247% from R411 (~$40) to R1015 (~$102), and women’s by 278% R 174 (~$17) to R 484 (about $48) (trend test, p  < 0.0001).…”
Section: Methodsmentioning
confidence: 99%
“…Prevalence of moderate or severe depression symptomatology and suicidal thoughts among men decreased significantly ( p  < 0.0001; p  = 0.01 respectively) [14]. Qualitative data from the pilot study suggested that women and men enjoyed participation in the intervention [20, 41]. In qualitative research primarily focused on men, men reported increased livelihood opportunities and greater savings [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…disputes, and population densities, present different barriers to violence prevention in informal settlements [8,68]. A small, but growing body of research focused on designing and testing violence prevention interventions in informal settlements in LMICs, mostly in South Africa [38,40,42,69,70], suggests that structural and behavioral interventions such as gender trainings and small-scale interventions, e.g. micro-loan programs, support groups, and joband skills-trainings, might be effective strategies to help to empower women and serve as models for larger future projects in these settlements [8].…”
Section: Plos Onementioning
confidence: 99%
“…Structural factors, particularly poverty, consistently undermines intervention attendance (Ringle et al, 2015;Williams et al, 2010). Poverty can operate in multiple ways, from creating conflict between work and work seeking, and session attendance (Gibbs, Jewkes, Mbatha, Washington, & Willan, 2014;Whittaker & Cowley, 2012;Williams et al, 2010), to participants lacking money to travel to sessions (Ringle et al, 2015). It is also plausible that youth living in the greatest poverty have poorer education levels , which may make intervention groups seem less familiar, friendly settings.…”
Section: Introductionmentioning
confidence: 99%